Antifungal effects of silver nanoparticles produced by Cinnamomum verum bark extract against fungi isolated from toothbrushes - Sahib, Raghad Ali; Obaid, Rasha Fadhel; Ali, Hiyam Adnan (Pharmakeftiki, 2025)
The findings revealed that 50 toothbrush samples used by individuals aged 20–50 years were contaminated with fungi. The infection rate was higher among females (40%), and fungal contamination increased when toothbrushes were used for more than three months. The most frequently isolated fungal species were Aspergillus niger (45%) and Penicillium citrinum (18%), while Fusarium oxysporum was the least common (2%). Silver nanoparticles (Ag NPs) were synthesized via a green method using Cinnamomum verum bark extract. The Ag NPs inhibited the growth of A. niger, A. flavus, A. terreus, and P. citrinum by 44.44%, 75.11%, 84.83%, and 98.66%, respectively, at a concentration of 200 µg/mL. Complete fungal inhibition was observed at 500 µg/mL, with statistically significant differences (p<0.05) compared to the untreated control.